Indonesian Local Learning Ecosystem in Energy Transition Era Ensure Wealth Stay in Local Economies - Suryadi, Erwin; Susanti, Ira (International Journal of Supply Chain Management, 2024)
The aim of this study is to elaborate the impact of collaborative work among stakeholders in Indonesia upstream oil gas industry for create value through supply chain management by prioritizing local products. Challenges of local products are not only from qualities and quantities as per industrial demands, but also from sustainable principles that start applying by Upstream Oil Gas Industry. The implementation of sustainable principles is very important to ensure that Indonesia can fulfil the target of energy transition as mentioned on the Paris Agreement in 2015. In this moment, Indonesia oil and gas industry and supported by the Government of Indonesia already prepared the roadmap to support the energy transition by reducing emissions, applying new technology for CCU/CCUS, and emphasizing the crucial role of the supply chain sustainability. As part of supply chain management (SCM) sustainability principles, the government and industry need to prepare the local companies to support the energy transition target. The landscape of the Indonesian petroleum industry, focusing on specific regulations for local content improvement and their alignment with supply chain sustainability in the energy transition era. Indonesian oil and gas companies operate under Production Sharing Contracts (PSC) with the government. The PSC has agreed to target local content with the government during exploration and operation. To achieve this, local companies must enhance their capabilities through research and development (RD) to remain competitive and support decarbonization strategies without compromising local content and emissions reduction initiatives. This paper discusses, according to the research, local companies have limitations to get access of new technologies that will be implemented during energy transition era. Therefore, collaborative work among Government and Industries is required to ensure local companies can be ready by the time the energy transition begins. Overcoming the challenge and limitation, this paper belief that collaboration among Government, Oil Gas Company, Supporting Industries (Vendor), Financial and Education Institution in Indonesia during the energy transition has pivotal role. By fostering collaboration, embracing sustainability principles, and investing in research and development, stakeholders can create a thriving ecosystem that supports local economic growth and environmental stewardship. Successful development programs through collaboration are ultimately expected to enhance job creation for Indonesian citizens, addressing the needs of the country with large population like Indonesia.